Evaluation of an online Gottman’s Psychoeducational intervention to improve marital communication among Iranian couples - Deylami, Neda; Hassan, Siti Aishah; Alareqe, Naser Abdulhafeeth; Zainudin, Zaida Nor (Multidisciplinary Digital Publishing Institute, 2021)
Amounting evidence indicates that insufficient knowledge of marital communication skills leads to destructive interactions and poor marital adjustments in couples, especially during stressful situations. Despite the high effectiveness of Gottman’s psychoeducational intervention, there is a lack of study on the online Gottman’s psychoeducation intervention (O-GPI) to improve marital communication and dyadic adjustments. The aim of this study was to evaluate the effectiveness of O-GPI on the improvement of marital communication patterns among Iranian couples. Method: The study followed a single-blind parallel group in a randomized controlled trial using an experimental longitudinal design, comprising 72 heterosexual couples living in Shiraz, Iran, with a 1–7-year marital age and no severe marital problems. The experimental group received eight consecutive O-GPIs via the Zoom platform, while the control group received information related to parenting skills via email. The outcome measures were the three patterns of communication: (i) constructive communication; (ii) demand–withdraw communication; and (iii) mutual avoidance communication—the screening measure was the dyadic adjustment scale. Results: The findings indicated that O-GPI could improve couples’ constructive communication significantly (45% for husbands and 40% wives) and decrease their total demand–withdrawal (51% for husbands and 65% wives) and mutual avoidance communication (60% for husbands and 62% wives). Limitations: Due to the homogenous nature of the sample, generalizations should be made with caution. Conclusions: This study demonstrates the feasibility and effectiveness of the online Gottman’s psychoeducational intervention to improve couples’ communication patterns.